2013
DOI: 10.1021/bi400222r
|View full text |Cite
|
Sign up to set email alerts
|

Structural Organization of FtsB, a Transmembrane Protein of the Bacterial Divisome

Abstract: We report the first structural analysis of an integral membrane protein of the bacterial divisome. FtsB is a single-pass membrane protein with a periplasmic coiled coil. Its heterologous association with its partner FtsL represents an essential event for the recruitment of the late components to the division site. Using a combination of mutagenesis, computational modeling and X-ray crystallography, we determined that FtsB self-associates and we investigated its structural organization. We found that the transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 80 publications
5
61
0
1
Order By: Relevance
“…The data shows that the TM region of the FtsB-FtsL complex is stably folded and that the TM helices are likely a major determinant for the association of the complex. We also show that FtsL and FtsB forms a 1:1 higher-order oligomeric complex, which is consistent with our previous hypothesis that the FtsB-FtsL complex is likely a tetramer 18 (Figure 1c). From these results, we hypothesize that the FtsB-FtsL complex may form a multi-valent binding hub that is important for the stabilization of the Z-ring.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…The data shows that the TM region of the FtsB-FtsL complex is stably folded and that the TM helices are likely a major determinant for the association of the complex. We also show that FtsL and FtsB forms a 1:1 higher-order oligomeric complex, which is consistent with our previous hypothesis that the FtsB-FtsL complex is likely a tetramer 18 (Figure 1c). From these results, we hypothesize that the FtsB-FtsL complex may form a multi-valent binding hub that is important for the stabilization of the Z-ring.…”
Section: Introductionsupporting
confidence: 92%
“…Previous studies indicate that both the transmembrane and the coiled coil domains are involved in their mutual association 6,7,17 . To investigate this we recently studied the structural organization of the individual domains of FtsB in isolation 18 . Using an in vivo interaction assay, we showed that the TM domain of FtsB self-associates in E. coli membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The complex can be studied using minimally altered, functional, full-length proteins in their natural environment. Extending the current data with photo cross-linking from FtsB and FtsL could provide clues concerning the FtsQBL stoichiometry and test, for instance, the recently reported structural organization of FtsB in vivo within the context of the membrane-spanning complex (44). Other divisome proteins can be added to the system to probe for other interaction interfaces, for instance at the site of the conserved DLRY(d/e)(s/t)G motif.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, the crystal structure of a fragment of FtsB comprising 30 membrane-proximal periplasmic amino acids was solved as a fusion with Gp7 showing a homodimeric helical form (38). However, the thermal stability of this dimer was low due to the few hydrogen bonds present.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the TM segments of the full-length FtsB and FtsL proteins are required for efficient interaction. The TMs may extend the predicted coiled coil structures in the respective periplasmic domains that are located directly adjacent to the membrane (11,18,38). To compensate for the absence of potentially interacting TM segments in our constructs, we fused artificial coils of opposite charge to the N terminus, a strategy that has proven successful to dimerize the soluble domains of DivIC and FtsL from Streptococcus pneumoniae that show some similarity to FtsB and FtsL of E. coli, respectively (24,39).…”
Section: Expression and Purification Of Ftsq P Ftsb P And Ftsl Pmentioning
confidence: 99%